2009
DOI: 10.1128/ec.00163-09
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Hyphal Formation and Virulence Assessed Using a Caenorhabditis elegans Infection Model

Abstract: Candida albicans colonizes the human gastrointestinal tract and can cause life-threatening systemic infection in susceptible hosts. We study here C. albicans virulence determinants using the nematode Caenorhabditis elegans in a pathogenesis system that models candidiasis. The yeast form of C. albicans is ingested into the C. elegans digestive tract. In liquid media, the yeast cells then undergo morphological change to form hyphae, which results in aggressive tissue destruction and death of the nematode. Severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
160
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(168 citation statements)
references
References 54 publications
7
160
0
1
Order By: Relevance
“…Previously, it was shown that hyphal form of C. albicans kills by piercing nematode cuticles, and that the yeast form is non‐lethal (Pukkila‐Worley et al ., 2009). Similarly, it was reported that the survival rates of C. albicans ‐infected nematodes were increased by treatment with gymnemic acid (Vediyappan et al ., 2013), retigeric acid (Chang et al ., 2012) or polyphenolic compounds such as magnolol and honokiol (Sun et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that hyphal form of C. albicans kills by piercing nematode cuticles, and that the yeast form is non‐lethal (Pukkila‐Worley et al ., 2009). Similarly, it was reported that the survival rates of C. albicans ‐infected nematodes were increased by treatment with gymnemic acid (Vediyappan et al ., 2013), retigeric acid (Chang et al ., 2012) or polyphenolic compounds such as magnolol and honokiol (Sun et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In some ways, this has similarity to its proliferation in the human gastrointestinal tract and gut translocation to cause invasive disease 15 . Pukkila-Worley, Peleg and colleagues have also shown the successful use of C. elegans in elucidating C. albicans dimorphism 7 . By employing hyphal defective mutant strains (EFG1 and FLO8) we showed that hyphae formation is necessary for the pathogenesis of Candida as confirmed by attenuated virulence toward C. elegans.…”
mentioning
confidence: 99%
“…One of the most important virulence factors that contribute to C. albicans pathogenesis is its ability to switch, reversibly, between yeast to filamentous (hyphal) forms 3 . The hyphal form of C. albicans is thought to be intricately related to its pathogenesis, with some studies showing that it is necessary for tissue destruction and invasion 3,[5][6][7] .…”
mentioning
confidence: 99%
See 2 more Smart Citations